2020
DOI: 10.1177/1059712320971372
|View full text |Cite
|
Sign up to set email alerts
|

Is it me or the room moving? Recreating the classical “moving room” experiment with virtual reality for postural control adaptation

Abstract: Postural control is a complex process requiring both sensory and motor responses. Perturbation-based balance training has emerged as an effective fall prevention intervention, which provides physical postural perturbations for postural control training and adaptation. With the advent of technology, virtual reality (VR) has also been used for fall prevention training by providing visual postural perturbations. This article addresses such VR studies, including a recent experiment which involved recreating the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These authors argued that their finding has implications for stability training and rehabilitation (cf. Chander et al, 2020). This is so because several applications are based on controlled perturbations of balance, which may be achieved in a convenient manner with a virtual moving room.…”
Section: Discussionmentioning
confidence: 99%
“…These authors argued that their finding has implications for stability training and rehabilitation (cf. Chander et al, 2020). This is so because several applications are based on controlled perturbations of balance, which may be achieved in a convenient manner with a virtual moving room.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the environment provide changing visual input, creating a sensory conflict between the visual, vestibular, and somatosensory-proprioceptive sensory systems of postural control. Any changes in the optic flow with a changing environment can induce an increase in postural sway, causing postural instability [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, incongruent visual information detected in relation to the body's spatial orientation results in postural instability [7,23]. More recently, visual manipulations in experimental and clinical settings use virtual reality (VR) to alter immersive virtual environments (VE) for rehabilitation [24]. VR has also been used to expose individuals to VE that can induce postural threats, such as simulated vertical heights [8,9,[25][26][27] and rotating the visual field on the pitch, yaw, and roll principle axes [26,28], that alter center of pressure (COP) dynamics and bodily kinematics and thereby, the overall postural stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous studies have not evaluated postural control dynamics of virtual claustrophobic environments. Taking inspiration from the classical "moving room paradigm" [23] and the proposed "virtual moving room paradigm" [24], more recently, the current researchers investigated the impact of unexpected and expected moving of a front wall in a virtual room on postural control dynamics [7]. The authors reported that postural sway increased during unexpected virtual perturbations and decreased during expected virtual perturbations, due to compensatory and anticipatory postural responses, respectively [7].…”
Section: Introductionmentioning
confidence: 99%